Association between AXIN1 Gene Polymorphisms and Bladder Cancer in Chinese Han Population - Li, Qin (Dis Markers, 2019)
BACKGROUND: Previous evidence has indicated that the reduction of axis inhibition protein 1 (AXIN1) expression is related with the poor differentiation of non-small-cell lung cancer (NSCLC). However, the potential association between AXIN1 and bladder cancer (BC) is unknown. We aimed to initially explore the relevance of AXIN1 gene polymorphisms (rs12921862 C/A, rs1805105 T/C, and rs370681 C/T) and BC. METHODS: Three hundred and sixteen BC patients and 419 healthy controls had been enrolled. Polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method was used for genotyping three tag single-nucleotide polymorphisms (SNPs) of AXIN1. The SNPstats online analysis software and SPSS software were used for statistical analysis. RESULTS: Our data revealed that three tag SNPs were associated with an increased risk of BC (rs12921862: P < 0.001, OR (95%CI) = 4.61 (3.13-6.81); rs1805105: P = 0.046, OR (95%CI) = 1.35 (1.00-1.82); and rs370681: P = 0.004, OR (95%CI) = 1.56 (1.15-2.10)). For rs12921862, A allele was an independently protective factor which correlated with a better prognosis in non-muscle-invasive bladder cancer (NMIBC) patients (P = 0.03, OR (95%CI) = 0.10 (0.01-0.84)). Stratification analysis demonstrated that rs370681 polymorphism was related with high-grade bladder cancer (P = 0.04, OR (95%CI) = 1.85 (1.04-3.23)). CONCLUSION: The AXIN1 gene polymorphisms might implicate in BC risk, and rs12921862 could be a potential forecasting factor for prognosis of BC patients.